2020
DOI: 10.1590/1806-9282.66.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin sodium pentahydrate combined with vacuum sealing drainage in the treatment of open fracture complicated with soft tissue injury

Abstract: SUMMARY OBJECTIVE To investigate the clinical efficacy of cefazolin sodium pentahydrate combined with vacuum sealing drainage (VSD) in the treatment of open fracture complicated with soft tissue injury. METHODS Sixty-three patients with open fracture complicated with soft tissue injury were divided into observation (n = 33) and control (n = 30) groups. After surgical reduction, fixation, and repair of the fractures, the control group was treated with VSD for 10 days, and the observation group was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, lymphocyte proliferation and apoptosis affect the maintenance of the number and ratio of various lymphocyte subsets as well as the general function of immunoregulation. Our results showed that the percentage of CD3 + CD4 + T lymphocytes and the ratio of CD3 Lou et al, 2020). Thus, we detected cytokine levels by ELISA and found that AECs possessed the ability to upregulate the concentrations of TNFα, IL-2, IL-6, IL-12, and IFNγ in splenocytes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, lymphocyte proliferation and apoptosis affect the maintenance of the number and ratio of various lymphocyte subsets as well as the general function of immunoregulation. Our results showed that the percentage of CD3 + CD4 + T lymphocytes and the ratio of CD3 Lou et al, 2020). Thus, we detected cytokine levels by ELISA and found that AECs possessed the ability to upregulate the concentrations of TNFα, IL-2, IL-6, IL-12, and IFNγ in splenocytes.…”
Section: Discussionmentioning
confidence: 55%
“…Activated splenocytes generate and sequentially secrete a variety of inflammatory cytokines to regulate the immune response. An increase in the level of one inflammatory factor can promote the synthesis and secretion of other inflammatory factors through a cascade reaction (Hye & Min, 2016 ; Jin‐Gyo et al., 2018 ; Lou et al., 2020 ). Thus, we detected cytokine levels by ELISA and found that AECs possessed the ability to upregulate the concentrations of TNF‐ α , IL‐2, IL‐6, IL‐12, and IFN‐γ in splenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently five generations of cephalosporins, mainly differentiated according to their structure, spectrum of activity and side-effect profile [ 1 ]. Cefazolin sodium pentahydrate, which belongs to the first generation of cephalosporin antibiotics, is an upgraded form of the traditional cefazolin sodium that further extends the strong anti-Gram-positive bacteria action of cefazolin sodium [ 2 ] and is suitable for the treatment of urinary tract, respiratory tract and biliary system infections. Previous studies have shown that cephalosporins such as ceftriaxone, cefotaxime and ceftazidime could induce urolithiasis [ 3–5 ].…”
Section: Introductionmentioning
confidence: 99%